Kinetic and Thermodynamics of the Removal of Zn2+ and Cu2+ from Aqueous Solution by Sulphate and Phosphate Modified Bentonite Clay - Unuabonah, Emmanuel (Elsevier, 2010)
The modification of pristine Bentonite clay with sulphate and phosphate anions was found to increase its cation-exchange capacity (CEC), adsorption capacity and overall pseudo-second order kinetic rate constant for the adsorption of Cu2+ and Zn2+. Modification with sulphate and phosphate anion decreased the specific surface area of pristine Bentonite clay. Phosphate-modified Bentonite clay was found to give the highest adsorption capacity for both metal ions. The adsorption process was observed to be endothermic and spontaneous in nature for both metal ions with Zn2+ being more adsorbed. Modification with phosphate anion increased the spontaneity of the adsorption process. The effective modification of pristine Bentonite clay with sulphate anion was confirmed from hypochromic shifts in the range of 13–18 cm−1 which is typical of physisorption while modification with phosphate anion was confirmed by its hyperchromic shifts typical of chemisorption in the infrared red region using Fourier transformed infrared spectroscopy (FTIR). Using the model efficiency indicator, kinetic data were found to show very strong fit to the pseudo-second order kinetic model implying that the adsorption of Cu2+ and Zn2+ were basically by chemisorption.
Keywords: Bentonite; Phosphate; Sulphate; Thermodynamics; Kinetics; Adsorption